we have -3q=5 so dividing both sides of the equation by -3 yields q=-5/3.
2p = 4y - 12xy - 6x, 3q = 12 - 15y so 2p - 3q = 4y - 12xy - 6x - (12 - 15y) = 4y - 12xy - 6x - 12 + 15y = 19y -12xy - 6x - 12
q=-6
3
3q+11+8q>99
3q + 2z, although it could be 2*(3q+z)
P = 3a - 3q Add 3q to each side: P + 3q = 3a Double each side: 6a = 2P + 6q
If -3q + 4 = 13 then 3q = -9 : q = -3 If 6q = 13 then q = 13/6 = 2 1/6 The question contains an anomaly and is invalid.
3q = 18 q = 6
2p = 4y - 12xy - 6x, 3q = 12 - 15y so 2p - 3q = 4y - 12xy - 6x - (12 - 15y) = 4y - 12xy - 6x - 12 + 15y = 19y -12xy - 6x - 12
q=-6
9q2 is the square of 3q - so 3q is the result of dividing 9q2 by 3q.
It can be simplified to 30pqr which means the same as the given terms
It is not an equation if it does not have an equals sign. You could simplify it but not solve it.
3q + 5 + 2q + 5 = 65 5q + 10 = 65 5q = 55 q = 11 Check it. 33 + 5 + 22 + 5 = 65 It checks.
(p-3q) (p-3q) =p2+3pq+3pq+9q2 =p2+6pq+9a2 this is answer hehehhe (jhaylotte)
3
steps to solve 4(3q-q): =(4)(3q+-q) =(4)(3q)+(4)(-q) =12q-4 answer: 8q